2021
DOI: 10.1101/2021.03.11.434989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information flows from hippocampus to auditory cortex during replay of verbal working memory items

Abstract: Background: The maintenance of items in working memory (WM) relies on a widespread network of cortical areas and hippocampus where synchronization between electrophysiological recordings reflects functional coupling. We investigated the direction of information between sensory areas and hippocampus during encoding and maintenance of WM items. Methods: Participants (N=15) performed a WM task where a string of letters was presented all at once, thus separating the encoding period from the maintenance period. P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…The SVM analysis showed that theta band-driven information flow is instrumental in maintaining WM information and in achieving correct performance. Theta oscillatory plays a crucial role in enabling inter-regional interactions (37) and information processing during WM (24, 38, 39). Computational models have suggested that theta oscillation coordinates the proper timing of interactions between the hippocampus and the EC (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SVM analysis showed that theta band-driven information flow is instrumental in maintaining WM information and in achieving correct performance. Theta oscillatory plays a crucial role in enabling inter-regional interactions (37) and information processing during WM (24, 38, 39). Computational models have suggested that theta oscillation coordinates the proper timing of interactions between the hippocampus and the EC (40).…”
Section: Discussionmentioning
confidence: 99%
“…The data set was analyzed and described earlier (4, 5, 11, 38) and is freely available for download at https://doi.gin.g-node.org/10.12751/g-node.d76994/. The task is freely available for download at http://www.neurobs.com/ex_files/expt_view?id=266.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Overall, our findings suggest that low frequency hippocampal activity contributes to the detection of auditory sequences and formation of auditory predictions. Low frequency activity in the hippocampus has been previously shown to mediate memory (E. L. Johnson et al 2018; Boran et al 2019; Dimakopoulos et al 2022) and predictions of future events (Sherman and Turk-Browne 2020). Our results expand the functions of low frequency hippocampal activity towards a role in maintaining an active model of environmental regularities.We found that the difference in hippocampal low frequency power between standard and deviant sounds increases the closer a sequence gets to a deviant sound, but only when the occurrence of a deviant sound can be predicted (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies can profit from recent advances of high-precision MEG to reconstruct subcortical activity (Tzovara et al 2019) and study how the medial temporal lobe network interacts with prefrontal regions. Another limitation of our study is that because of the tight timing in our experimental setup we were not able to assess metrics of functional connectivity among our three target regions, which typically rely on oscillatory coupling, that evolves over longer temporal intervals (Dimakopoulos et al 2022). Our findings on the timing of onsets and peaks auditory responses and deviance effects provide a first indication on the information flow in the amygdalo-hippocampal-temporal network, that can be confirmed using longer sound intervals.…”
Section: Discussionmentioning
confidence: 99%
“…In this pursuit, several statistical methods have been developed at each scale of the electrophysiological measures - spiking and local field potentials (LFPs). In LFPs, Granger causality studies have implicated distinct frequency bands in several neurophysiological phenomena, including predictive routing (Pelt et al 2016; Andr é M Bastos, Lundqvist, et al 2020), top-down and bottom-up signal processing (Gregoriou et al 2009; Andre Moraes Bastos et al 2015; Richter, Coppola, and Bressler 2018; Ferro et al 2021), and working memory (Popov, Jensen, and Schoffelen 2018; Dimakopoulos et al 2022). Pairwise correlations between single neurons have identified network organization consistent with anatomical connectivity (Tanaka 1983; Alonso, Usrey, and Reid 1996; Z.…”
Section: Introductionmentioning
confidence: 99%